Wood Microstructure Studies of the Order Oxalidales from Erstwhile India - Gupta, Sangeeta; Saxena, Vishakha (Indian Forester, 2011)
The order Oxalidales has been divided into 6 families, out of these 2 families are represented in India viz. Elaeocarpaceae and Oxalidaceae. The present study deals with detailed wood microstructure of both families. 18 species and 2 genera of the family Elaeocarpaceae and single species belonging to single genus of the family Oxalidaceae have been described for their detailed wood microstructure, salient diagnostic features and photomicrographs. Wood anatomical studies also support the grouping of both the families together.